Die "Malebochoorlog" van 1894 : waarnemingsvermoë as kriteriurn vir die betroubaarheid van bronne (Historia, 2021)
EnglishThe "Maleboch War" of 1894 : the ability to observe as criterion for the reliability of sources In the light of the renewed interest in Blouberg's Hananwa under Mmalebôhô just more than a hundred years after the "Maleboch War" which was waged by the Z.A.R., it has become necessary to look into the reliability of the sources most frequently used by researchers working on this 1894 conflict. This article compares the reliability of two published diaries which were written on the campaign by Reverend Colin Rae and missionary Christoph Sonntag respectively. The ability of each of these witnesses to observe is applied as criterion for testing the reliability of their respective accounts of the conflict. The influence of personal subjectivity on their reliability in each case is considered before Rae and Sonntag are compared with respect to their physical ability to observe on the one hand, and their social ability to do so, on the other. Under social ability, an attempt is made to determine which witness's knowledge of language, his familiarity with military affairs and his sensitivity for the diverse cultures of the warring parties, enables him to make the most reliable observations. In conclusion, it does not seem feasible or desirable to appoint one of the witnesses as being more reliable under all circumstances. This would imply disregard for the fact that an unique combination of factors influences each incident observed by the witnesses in a different way. However, considering Sonntag's conscientious personality, his acute awareness of different culturalframeworks and his better knowledge of the terrain of the conflict, he can, in general terms, be regarded as the more reliable witness.  AfrikaansIn die lig van die hernude belangstelling in Blouberg se Hananwa onder Mmalebôhô pas honderd jaar na die "Maleboch-oorlog" wat die Z.A.R. gevoer het, is dit nodig om te vra na die betroubaarheid van die vernaamste bronne wat deur navorsers omtrent die 1894-konflik geraadpleeg word. In hierdie artikel word eerwaarde Colin Rae en sendeling Christoph Sonntag se gepubliseerde dagboekweergawes van die veldtog met mekaar vergelyk ten opsigte van die betroubaarheidskriterium waarnemingsvermoë. Die invloed van persoonlike subjektiwiteit op die waarnemers se betroubaarheid word oorweeg voordat Rae en Sonntag ten opsigte van hulle fisiese vermoëns aan die een kant, en hulle sosiale vermoëns aan die ander kant, vergelyk word. Onder laasgenoemde, word gepoog om vas te stel watter getuie se talekennis, militêre kennis en begrip vir die teenoorstaande partye se uiteenlopende kulture, hom tot die betroubaarste waarneming in staat gestel het. Ten slotte, blyk 'n algemeen-geldende beslissing ten gunste van die betroubaarheid van die een getuie, teenoor die onbetroubaarheid van die ander, problematies te wees. Só 'n beslissing, sou neerkom op 'n miskenning van die unieke samestelling van faktore wat die waarnerning van elke afsonderlike insident verskillend beïvloed. Tog kan Sonntag, op grond van sy konsensieuse persoonlikheid, sy skerp ingesteldheid op verskillende kulturele raamwerke en sy beter vertroudheid met die oorlogsmilieu, as die oorwegend betroubaarder waarnemer aangewys word.
Keywords: Lize Kriel; 1894-konflik; Colin Rae; Christoph Sonntag; Maleboch War; Suid-Afrika; Venda; Mphephu; Blouberg